Nazi cinema as enchantment : the politics of entertainment in the Third Reich - O'Brien, Mary-Elizabeth 1959- (Studies in German literature, linguistics, and culture, 2004)
1. History, Utopia, and the social construction of happiness -- 2. Mapping German identity -- 3. The celluloid war -- 4. Discontented domesticity -- 5. The forbidden desires of everyday life